A local projection for integrating geodetic and terrestrial coordinate systems. Issue 374 (2nd September 2020) - Bremner, Mike; Santos, Marcelo
Abstract : This paper develops a system for projecting coordinates from a geocentric coordinate system to a topocentric coordinate system defined by terrestrial measurements. The proposed system uses an extension of the Stereographic Double Map Projection and a parametric least squares estimation to calculate the parameters for the map projection. The Extended Stereographic Double Projection and the projection parameter estimation are implemented and tested. Tests are performed to determine rate that discrepancies occur and the maximum extents of the Extended Stereographic Double Projection. This maximum area is determined to be ∼10 km 2 with RMS values of residuals of 0.0029 m in northing and 0.0020 m in easting. Tests are also performed to determine the factor that limits the effective area of the Projection.